Zurich University Hospital lung transplantation programme: update 2012 (Swiss Medical Weekly, 2013)
Lung transplantation is an established therapeutic option for end-stage lung disease in selected patients. During the last 30 years more than 34,000 transplantations have been performed worldwide. Emphysema, pulmonary fibrosis, cystic fibrosis and primary pulmonary hypertension are the most common indications. This type of surgical treatment is increasingly successful, with better early and late survival rates. However, lung transplantation is still hampered by persisting problems such as donor organ shortage, primary graft dysfunction, late graft dysfunction and morbidity related to long-term immunosuppression. The first lung transplantation in Switzerland was performed the 10th November 1992 at Zurich University Hospital. Since then the lung transplant programme has progressively increased its yearly transplant volume. Since the beginning of our lung transplantation programme, overall patient survival has increased steadily and has been at benchmark levels since the year 2000. The most important factors influencing this result are presumably good teamwork among all involved specialists, improved surgical techniques, and close and long-term patient follow-up by the transplant pulmonologists. In this paper we present our programme structure, managing strategies for some specific problems and outcome after lung transplantation. The results presented here are from recipients who underwent lung transplantation up to the end of 2011.